2021
DOI: 10.1074/jbc.ra120.014618
|View full text |Cite
|
Sign up to set email alerts
|

Multivalent lipid targeting by the calcium-independent C2A domain of synaptotagmin-like protein 4/granuphilin

Abstract: Synaptotagmin-like protein 4 (Slp-4), also known as granuphilin, is a Rab effector responsible for docking secretory vesicles to the plasma membrane before exocytosis. Slp-4 binds vesicular Rab proteins via an N-terminal Slp homology domain, interacts with plasma membrane SNARE complex proteins via a central linker region, and contains tandem C-terminal C2 domains (C2A and C2B) with affinity for phosphatidylinositol-(4,5)-bisphosphate (PIP 2 ). The Slp-4 C2A domain binds with low nanomol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(28 citation statements)
references
References 70 publications
0
28
0
Order By: Relevance
“…Specifically, Rab27a and its effector Slp4 function in docking of MVBs on plasma membrane, and Rab27b and its effector Slac2b mediate the transfer of MVBs from the perinuclear area to the cell periphery [107]. Slp4 (also known as granuphilin) interacts with Rabs via its N-terminal Slp homology domain and binds to SNARE complex via a central linker region [108]. Park et al reported that disrupting the interaction between Rab27a and Slp4 with inhibitor BHMPS reduced exosome secretion and inhibited tumor growth of breast cancer cells [109].…”
Section: Rab Gtpasesmentioning
confidence: 99%
“…Specifically, Rab27a and its effector Slp4 function in docking of MVBs on plasma membrane, and Rab27b and its effector Slac2b mediate the transfer of MVBs from the perinuclear area to the cell periphery [107]. Slp4 (also known as granuphilin) interacts with Rabs via its N-terminal Slp homology domain and binds to SNARE complex via a central linker region [108]. Park et al reported that disrupting the interaction between Rab27a and Slp4 with inhibitor BHMPS reduced exosome secretion and inhibited tumor growth of breast cancer cells [109].…”
Section: Rab Gtpasesmentioning
confidence: 99%
“…There have been a number of MD studies of the interaction of Ca 2+ -dependent C2 domains with membranes, revealing how Ca 2+ ions mediate interactions between the protein and anionic lipids such as phosphatidylserine (PS) and phosphatidylinositol phosphates (PIPs) ( Alwarawrah and Wereszczynski, 2017 ; Banci et al., 2002 ; Chon et al., 2015 ; Jaud et al., 2007 ; Lai et al., 2010 ; Manna et al., 2008 ; Michaeli et al., 2017 ; Vermaas and Tajkhorshid, 2017 ). However, there have not been many simulation studies of the interactions of Ca 2+ -independent C2 domains with membranes (see, e.g., Alnaas et al., 2021 ; Scott et al., 2020 ) other than for PTEN ( Shenoy et al., 2012a ; Treece et al., 2020 ), despite the growing recognition of the importance of such interactions in a number of cellular processes ( Stahelin et al., 2014 ). Here, we use coarse-grained molecular dynamics (CG-MD) ( IngĂłlfsson et al., 2014 ; Marrink and Tieleman, 2013 ) to examine and compare the interactions of six different Ca 2+ -independent C2 domains with lipid bilayers: C2 domains from KIBRA (PDB: 6FJD ), PI3KC2α (PDB: 6BU0 ), RIM2 (PDB: 2BWQ ), PTEN (PDB: 1D5R ), Smurf2 (PDB: 2JQZ ), and SHIP2 (PDB: 5OKM ).…”
Section: Introductionmentioning
confidence: 99%
“… Twenty micrograms of recombinant p62 was treated with 4-HNE (molar ratio of 1:10) for 60 min, digested with trypsin, and analyzed using LC-MS/MS as previously described [ 28 , 44 ]. 4-HNE adducted residues are denoted in red (N = 3).…”
Section: Resultsmentioning
confidence: 99%